Investigating rolling as mechanism for humeral fractures in non-ambulant infants: a preliminary finite element study. Issue 1 (January 2020) - Altai, Z.; Viceconti, M.; Li, X.; Offiah, A.C.
Abstract : AIM: To use personalised computed tomography (CT)-based finite element models to quantitatively investigate the likelihood of self-inflicted humeral fracture in non-ambulant infants secondary to rolling. MATERIALS AND METHODS: Three whole-body post-mortem CT examinations of children at the age of rolling (two 4-month-old and one 6-month-old) were used. The mechanical moment needed by each infant to perform a rolling manoeuvre was calculated and applied to the finite element model in order to simulate spontaneous rolling from the prone to the supine position. RESULTS: The maximum predicted strains were found to be substantially lower (with a difference of >80%) than the elastic limit of the bone. CONCLUSION: Results of this study challenge the plausibility of self-inflicted humeral fracture caused by rolling in non-ambulant infants and indicate that it is unlikely for a humeral fracture to result from this mechanism without the assistance of an external force. Highlights: Humeral fractures are unlikely to occur in non-ambulant infants through rolling without external intervention. An additional relativity small external force is required to fracture the humerus. Inflicted injury should be considered as differential diagnosis if such a history is given by the carer(s).